Molecular analysis of the tlyA gene in Campylobacter lari - Matsubara, Keiko; Nakajima, Takuya; Moore, John E; Millar, Beverley C; Murayama, Tsugiya; Matsuda, Motoo (Folia microbiologica, 2015)
Full-length tlyA gene and its adjacent genetic loci from the urease-positive thermophilic Campylobacter (UPTC) CF89-12 [approximately 15,000 base pairs (bp) in length], as well as a reference strain Campylobacter lari RM2100 (approximately 9,000 bp), were analyzed. The possible open-reading frame of tlyA from UPTC CF89-12 was shown to have 720 bp with a calculated molecular mass of approximately 26.7 kDa. Using a primer pair designed in silico, a total of approximately 1.1 kbp consisting of putative promoter region, structural gene for tlyA, and its adjacent genetic loci were identified in all 17 C. lari isolates [n = 13 for UPTC; n = 4 for urease-negative (UN) C. lari]. Although sequence differences were demonstrated at approximately 20 loci within the 90 bp non-coding (NC) region, including the putative promoter structure candidates immediately upstream of the tlyA gene among the 18 isolates including C. lari RM2100, no sequence differences were identified within the NC region among the five UN C. lari isolates examined. A start codon ATG and a probable ribosome-binding site, AGGC(T)GG(A), for the tlyA gene were identified in all 18 isolates, including C. lari RM2100. The putative intrinsic ρ-independent transcriptional terminator structure candidate was also identified for the tlyA gene in both UPTC CF89-12 and C. lari RM2100. Additionally, the hemolysis assay was performed with some of the C. lari isolates. The tlyA gene nucleotide sequence data may possibly be useful for discrimination between UN C. lari and UPTC organisms, as well as for the differentiation among the four thermophilic Campylobacter species.
Keywords: Campylobacter lari; kur domácí; Animals; otevřené čtecí rámce; Base Sequence; Birds; Chickens; Bivalvia; sekvence aminokyselin; bakteriální proteiny; Bacterial Proteins; Molecular Sequence Data; mlži; Hemolysin Proteins; kampylobakterové infekce; hemolyziny; Amino Acid Sequence; Campylobacter Infections; ptáci; Phylogeny; molekulární sekvence - údaje; Sequence Alignment; sekvence nukleotidů; promotorové oblasti (genetika); zvířata; Open Reading Frames; Promoter Regions, Genetic; fylogeneze; sekvenční seřazení; mikrobiologie životního prostředí; Environmental Microbiology